The influence of conceptual concreteness on the reading acquisition and integration of novel words into semantic memory via thematic relations - Ding, Jinfeng; Liang, Panpan; Guo, Xinyu; Yang, Yufang (Frontiers in Psychology, 2023)
Plenty of studies have been conducted to reveal neurocognitive underpinnings of conceptual representation. Compared with that of concrete concepts, the neurocognitive correlates of abstract concepts remain elusive. The current study aimed to investigate the influence of conceptual concreteness on the reading acquisition and integration of novel words into semantic memory. We constructed two-sentence contexts in which two-character pseudowords were embedded as novel words. Participants read the contexts to infer the meaning of novel words which were either concrete or abstract, and then performed a lexical decision task and a cued-recall memory task. In lexical decision task, primed by the learned novel words, their corresponding concepts, thematically related or unrelated words as well as unlearned pseudowords were judged whether they were words or not. In memory task, participants were presented with the novel words and asked to write down their meaning. The contextual reading and memory test can demonstrate the modulation of conceptual concreteness on novel word learning and the lexical decision task can reveal whether concrete and abstract novel words are integrated into semantic memory similarly or not. During contextual reading, abstract novel words presented for the first time elicited a larger N400 than concrete ones. In memory task, the meaning of concrete novel words was recollected better than abstract novel words. These results indicate that abstract novel words are more difficult to acquire during contextual reading, and retain afterwards. For lexical decision task behavioral and ERPs were graded, with the longest reaction time, the lowest accuracy and the largest N400s for the unrelated words, then the thematically related words and finally the corresponding concepts of the novel words, regardless of conceptual concreteness. The results suggest that both concrete and abstract novel words can be integrated into semantic memory via thematic relations. These findings are discussed in terms of differential representational framework which posits that concrete words connect with each other via semantic similarity, and abstract ones via thematic relations.